Mucosal cellular regeneration and colorectal carcinogenesis - Simanowski, Ulrich; Wright, Nicholas A.; Seitz, Helmut K. (Colorectal cancer: from pathogenesis to prevention?, 1989)
Altered cellular regeneration is the prominent feature that distinguishes cancer from normal tissue. Therefore it is of paramount importance to understand cell regeneration and its regulation in normal colonic mucosa during carcinogenesis and in carcinomas if we want to design and evaluate new therapeutic measures. Cell proliferation and its measurement has been the domaine of histology. However, recent years have seen increasing attempts to link molecular biology to cell cycle events and regulation of cell proliferation, which will be dealt with elsewhere.